The Role of Parents in the Religious Education of Children in Dusun II Kagungan Ratu Village, Tulang Bawang Udik District West Tulang Bawang Regency - Ihsan Asrofi; Zainal Arifin; Adi Wijaya (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
This research is motivated by the importance of the role of parents as primary educators in children's religious education, particularly in Dusun II, Kagungan Ratu Village, Tulang Bawang Udik District, West Tulang Bawang Regency. Lifestyle changes, the influence of technology, and time constraints pose challenges that can reduce the intensity and quality of religious education at home. This study aims to describe the role of parents in children's religious education, identify the obstacles faced, and discover effective approaches that can be applied. The research employs a qualitative method with descriptive field research. Data were collected through in-depth interviews, observation, and documentation. Purposive sampling was used to select four families who met the criteria. Data analysis was conducted interactively through data reduction, data presentation, and conclusion drawing and verification, using technique and source triangulation. The results show that the role of parents includes providing role models, teaching religious values, habituating worship practices, and creating a religious environment at home. Obstacles faced include time constraints due to work, low consistency in role modeling, and the negative influence of technology and the environment. Despite this, parents strive to overcome these challenges through strategies such as positive habituation, strict supervision, and involving children in religious activities. This study recommends increasing awareness and providing support for parents so they can carry out their roles optimally in shaping children's religiosity.